Manajemen Mutu Terpadu dalam Pendidikan Islam - Al-Ikhlas Al-Ikhlas; Ujang Sayuti; Andi Fery; Ahmad Sabri; Hidayati Hidayati (Departement of Mathematics Education, 2023)
Total Quality Management (TQM) or Integrated Quality Management in the field of Islamic education has the ultimate goal of improving quality and competitiveness for output (graduates) with indicators of competency both intellectual and skill as well as high social competence of students/graduates. In achieving these results, the implementation of TQM in Islamic education organizations needs to be done truthfully, not half-heartedly. By utilizing all the quality entities that exist within the organization, our education will not run where it is today. Implementation of TQM in educational organizations, especially in Islamic educational institutions, is not easy. There are obstacles in the work culture, the performance of teachers and employees is very influential. There is no denying that the work culture, performance and discipline of civil servants in our country is very low. This greatly affects the effectiveness of TQM implementation. This study uses the approach of the concept of Integrated Quality Management and the concept of Quality Management in Islamic Education. While this research uses library research methods, and qualitative methods. This research is expected to be able to provide input and good knowledge of new knowledge for the world of education, especially in Islamic education.